Juvenile multicentric leukosis in a heifer from the State of Pará, Brazil - Barbosa, José Diomedes; Lopes, Cinthia Távora de Albuquerque; de Brito, Adriel Behn; Silva, Rafaela das Merces; Reis, Alessandra dos Santos Belo; Oliveira, Carlos Magno Chaves; Salvarani, Felipe Masiero (Brazilian Journal of Veterinary Medicine, 2016)
ABSTRACT. Barbosa J.D., Lopes C.T.A., Brito A.B., Silva R.M., Reis A.S.B., Oliveira C.M.C. & Salvarani F.M. [Juvenile multicentric leukosis in a heifer from the State of Pará, Brazil.] Leucose bovina multicêntrica juvenil em uma bezerra no Estado do Pará, Brasil. Revista Brasileira de Medicina Veterinária, 38(1):57-60, 2016. Programa de Pós-Graduação em Ciência Animal, Instituto de Medicina Veterinária, Universidade Federal do Pará, BR 316, Km 61, Cristo Redentor, Castanhal, PA 68740-970, Brasil. E-mail: diomedes@ufpa.br The purpose of this paper is to describe the clinical and pathological findings of the first case of juvenile multicentric sporadic leukosis diagnosed in the Amazon biome in a 35 days old heifer, in the county of Santa Izabel, State of Pará, Brazil. The diagnosis was made by the Veterinary Diagnostic Center team from the Federal University of Pará and after clinical evaluation, blood samples were collected for hemogram. The results were decreased count of red blood cells and severe leukocytosis by lymphocytosis. The animal euthanasia was conducted due to poor prognosis. At necropsy, fragments of all organs were collected, fixed in 10% buffered formalin for histopathological examination. The histological analysis revealed infiltration of neoplastic lymphocytes in the liver, spleen and kidney parenchyma. The clinical and pathological findings led to the diagnosis of juvenile multicentric sporadic leukosis.